2019
DOI: 10.3390/su11061797
|View full text |Cite
|
Sign up to set email alerts
|

Using Structural Equation Modeling to Propose a Model for Shopping Complex Design Based on Universal Design Concept

Abstract: Universal design (UD) is a design style that promotes the design for all people regardless of their abilities and sociodemographic features. The UD is also viewed as an element of social sustainability. Shopping complexes, as one of the main places for leisure activities, can be designed and assessed based on UD to enhance the usability for all shoppers. At present, no clear definition of UD is available in shopping complex design criteria. Consequently, a very limited number of design and assessment guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There are several shopping malls in the Kurdish part of Iraq, which have not been assessed for adherence to the UD principles. Literature also confirms that, to date, there is no systematic approach to assess the suitability of shopping malls in Iraq, particularly the Kurdish Part (Jalil Abdullah and Jian 2019). This paper presents a part of wider research endeavor to leverage the use of UD in the design and assessment of shopping malls in Kurdish part of Iraq.…”
Section: Tang Jian and Rebaz Jalil Abdullah -International Journal Of Bmentioning
confidence: 57%
See 1 more Smart Citation
“…There are several shopping malls in the Kurdish part of Iraq, which have not been assessed for adherence to the UD principles. Literature also confirms that, to date, there is no systematic approach to assess the suitability of shopping malls in Iraq, particularly the Kurdish Part (Jalil Abdullah and Jian 2019). This paper presents a part of wider research endeavor to leverage the use of UD in the design and assessment of shopping malls in Kurdish part of Iraq.…”
Section: Tang Jian and Rebaz Jalil Abdullah -International Journal Of Bmentioning
confidence: 57%
“…This paper presents a part of wider research endeavor to leverage the use of UD in the design and assessment of shopping malls in Kurdish part of Iraq. The authors identified and confirmed the contributory design factors of shopping malls to the UD principles in Jalil Abdullah and Jian (2019). In this paper, the authors aim to illustrate the development process of a tool for assessing the shopping malls in Kurdish part of Iraq based on UD concept.…”
Section: Tang Jian and Rebaz Jalil Abdullah -International Journal Of Bmentioning
confidence: 88%
“…This boundary might influence their expectations, attitudes, and feelings toward the city and its inhabitants. City entrances serve as the initial points of contact for both residents and visitors, influencing their first impressions and overall experience of the city [20,27]. By investigating the cognitive and emotional aspects associated with city entrances, this research aims to uncover how these symbolic gateways contribute to the formation of a city's identity.…”
Section: B Entrance As a Mental Boundary Of A Citymentioning
confidence: 99%
“…It might explore how the first impression of a city gained through its entrance impacts the overall perception of the city. The city entrance stands as a proud witness to the passage of time, encapsulating the very essence and soul of a city within its impressive arches and facades [27,28]. These gateways are not mere structures; they extend an open invitation for all to explore the city's unique blend of history, culture, architecture, and aspirations.…”
Section: Entrance As a Window To Look At A Citymentioning
confidence: 99%
“…Global studies are more focused on catering to the needs of disabled people rather than considering facilitating the needs of all user groups by considering universal design considerations [29]. Abdallah and Jian (2019) consider usability, safety, and comfort in the quantitative analysis of universal design in shopping malls [30]. More specifically, planning the means of escape in shopping malls, including alignment with building code, emergency evacuation, manual call points, alarms, and fire safety signage, is of utmost importance.…”
mentioning
confidence: 99%